Analisis Penerapan Total Quality Management (TQM) Dalam Meningkatkan Kualitas Produk pada Percetakan Delaux Paper di Gunungsitoli - Mei Warni Laoli; Martha S. D. Mendrofa; Idarni Harefa; Eduar Baene (Journal on Education, 2024)
Total Quality Management (TQM) is an integrated management system that emphasizes quality improvement as a company strategy that aims to ensure customer satisfaction by involving all parts of the organization. This research aims to determine the application of TQM, determine product quality, and determine product quality improvement at Delaux Paper printing in Gunungsitoli City. The research method used is descriptive research. Based on research results, implementing TQM requires commitment from the entire organization. In printing, all employees must be involved in efforts to improve product quality. Training, building a quality culture, and active participation of all team members are essential in creating an environment that supports continuous product quality improvement. TQM helps printers to achieve significant product quality improvements and Data-based performance measurement is a key component of TQM, by collecting and analyzing data about product quality, printers can identify problems, track progress and take appropriate corrective action. Effective use of data helps printers make decisions based on facts and evidence, and directs continuous improvement efforts.